Attractive nanofiber structure based on Cu-Ti/metal sandwich film with excellent electrocatalytic performance for ethanol oxidation. (1st December 2020) - Hu, Qingzhuo; Zhang, Fabao; Zhang, Jinjun; Jiang, Wei; Zhang, Bo
Abstract: The support materials are an important part of catalysts and they are the dispersant, adhesive, and support for other components. In this study, three types of thin films with different structures were used as the precursor to prepare loading Pd catalysts. The one-step dealloying method was used to prepare a semiconductor nanofiber film (NFF) support material with upward directional growth from the substrate. Pd/NFF and Pd/NiO/NFF loaded Pd catalysts were prepared using NFF as the support material, and the electrochemical catalytic properties for ethanol oxidation in alkaline media were studied. Cyclic votammetry showed that the NFF support material effectively inhibited agglomeration of palladium, increased the number of active sites of Pd, and improved the electrocatalytic properties of Pd for ethanol oxidation. In addition, the Pd/NiO/NFF loaded Pd catalyst obtained by modification with nickel oxide significantly improved the electrocatalytic performance for ethanol oxidation compared with the Pd/NFF loaded Pd catalyst. These results show that NiO is conductive to absorption of oxygen-containing groups on the surface of the catalyst and can further improve the electrocatalytic ability of Pd for ethanol oxidation. All of the above results demonstrate that the support material prepared by the dealloying method has application prospects in load-type catalysts.